Merkel cell carcinoma and follicular lymphoma: A highly unusual collision tumor - Suknuntha K. (2023)
Merkel cell carcinoma (MCC), a rare and aggressive skin tumor, has a tendency to occur in association with hematologic malignancies, in particular chronic lymphocytic leukemia (CLL). The permissive immunologic environment and Merkel cell polyoma virus infection has been postulated as part of MCC pathogenesis. A collision tumor consisting of follicular lymphoma (FL) and MCC has never been described. Here we report an unusual case of nodal MCC of unknown primary arising in an immunocompetent patient who had FL involving multiple lymph nodes. Similar to the FL, PAX-5 and BCL2 were also expressed in the MCC. Cytogenetic and molecular studies showed that the two neoplastic processes are clonally unrelated. We also demonstrated a pathogenic PTEN mutation that has not been previously reported in MCC, associated with loss of heterozygosity due to monosomy 10. Our mutation data suggests that MCC of unknown primary may be pathogenetically related to typical cutaneous MCC.